2000
DOI: 10.1007/s11661-000-0272-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu content and preaging on precipitation characteristics in aluminum alloy 6022

Abstract: Effects of Cu content and preaging treatments on precipitation sequence and artificial aging response in aluminum alloy 6022 were investigated using transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and hardness tests. It was found that Cu induces the formation of Q and its precursor metastable phases and has a beneficial effect on the kinetics of artificial aging. For the alloy with 0.07 wt pct Cu, the precipitation sequence is GP zones → needlelike ␤ Љ → rodlike ␤ Ј ϩ lathlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
122
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(146 citation statements)
references
References 19 publications
18
122
0
6
Order By: Relevance
“…This is in good agreement with previous results showing that Cu additions enhance material hardness [10,24], and demonstrates that 0.10 wt% Cu addition is a quantity large enough to produce a measurable effect.…”
Section: Resultssupporting
confidence: 93%
“…This is in good agreement with previous results showing that Cu additions enhance material hardness [10,24], and demonstrates that 0.10 wt% Cu addition is a quantity large enough to produce a measurable effect.…”
Section: Resultssupporting
confidence: 93%
“…Peak III, IV and V are described to the formation of ¢AA, ¢A metastable precipitates and the equilibrium precipitates ¢-(Mg 2 Si). These results are in good agreement with those of Miao et al 11) and Gaber et al 12) It is found that the peak area and peak temperature are changed depending on the Si concentration. In this paper, peak I corresponding to the formation of nanoclusters is mainly focused and discussed because nanoclusters play important roles in AlMgSi alloys.…”
Section: +1supporting
confidence: 92%
“…It would be interesting, for example, to compare the silver addition with reports about the effect of copper addition to this alloy on precipitation. [5][6][7] In our recent study, an Al-1.0 mass%Mg 2 Si-0.5 mass%Ag alloy showed good ductility at peak aged condition as compared with peak aged Al-1.0 mass%Mg 2 Si alloy. 3) On the other hand, a new grain boundary precipitate has been found in an Al-1.0 mass%Mg 2 Si-0.5 mass%Ag alloy by HRTEM method, 8) designated as a quaternary Al-Mg-Si-Ag compound (the Q Ag -phase), similar to the Q 0 -phase in Al-Mg-SiCu alloys.…”
Section: Introductionmentioning
confidence: 85%
“…3) On the other hand, a new grain boundary precipitate has been found in an Al-1.0 mass%Mg 2 Si-0.5 mass%Ag alloy by HRTEM method, 8) designated as a quaternary Al-Mg-Si-Ag compound (the Q Ag -phase), similar to the Q 0 -phase in Al-Mg-SiCu alloys. [5][6][7] An addition of silver to this alloy also seems to affect nucleation 4) according to a differential scanning calorimetric (DSC) analysis.…”
Section: Introductionmentioning
confidence: 99%